EFL Students’ Grammatical Errors in Writing Descriptive Text - Arisman Arisman (International Journal of Innovation and Education Research, 2023)
The aim of this study is to find out grammatical most frequently made by the student in writing descriptive text. This study was quantitative and qualitative method. The population of this study is Students' English Department of Muhammadiyah University. The writer chose 23 students as the sample. In this study, collect the data used observation, writing test, and documentation. The result shows there were 328 items of error in the students’ writing. The percentage of errors made by students in writing descriptive text are noun phrase 49,7%, verb phrase36,3%, adjective phrase 8,8%and adverb phrase5,2%. The writer finds that the grammar errors that most of the students made were in noun phrases, with a cumulative total of 163 errors or 49.7%. From the research findings, it is suggested learners have to use these errors as a means to study more about correct the use of grammar in descriptive texting, especially in the use of noun phrases, verb phrases, and adjectives. For teachers to work harder on noun phrases and verb phrases because they are the most frequent failures that are made by students in their writing.